Patient experience and satisfaction with admission to an acute geriatric community hospital in the Netherlands: a mixed method study. Issue 4 (30th November 2021) - Ribbink, Marthe E.; Roozendaal, Catharina C.; MacNeil-Vroomen, Janet L.; Franssen, Remco; Buurman, Bianca M.
Abstract : Purpose: The acute geriatric community hospital (AGCH) in an intermediate care facility is an alternative to conventional hospitalization. A comprehensive geriatric assessment and rehabilitation are integrated into acute medical care for older patients. This study aims to evaluate patient experience and satisfaction with the AGCH. Design/methodology/approach: This is a mixed method observational study including a satisfaction questionnaire and qualitative interviews with AGCH patients or informal caregivers. Findings: A total of 152 participants filled in the questionnaire, and thirteen semi-structured interviews were conducted. Twelve categories and four overarching themes emerged in the analysis. In general, study participants experience the admission to the AGCH as positive and are satisfied with the care they received; there were also suggestions for improvement. Research limitations/implications: Limitations of this study include possible participation bias. The results show that patients value this type of care indicating that it should be implemented elsewhere. Further research will focus on health outcomes, readmission rates and cost effectiveness of the AGCH. Originality/value: This is the first study to evaluate care satisfaction with the AGCH. It shows that hospitalized older adults positively value the AGCH as an alternative to hospitalization.